REFLECTION ON ENGLISH TEACHER TRAINING PROGRAM (Jurnal Pengabdian Masyarakat AbdiMas, 2023)
In teacher education, one of the important programs is student internship at a school. This program aims at preparing pre-service teachers with sufficient working experience at a school so they will be able to apply theories and principles of teaching in a classroom. To achieve this goal, pre-service teachers must be able to conduct reflection. Reflection is a key to achieve a successful internship at a school. The purpose of the present community service program is to socialize the roles of reflection in teacher training education. Particularly, the reflection was conducted by the students of the English Language Education Study Program at Esa Unggul University. The students took their internship at junior high schools in Jakarta. The socialization is a collaboration with ASEAN Lecturer Community. It is conducted by doing a webinar. The participants are lecturers, teachers, and university students. At the end of the socialization, the participants are aware of the importance of reflection as a part of teaching in a class because it can develop their professional competence as teachers.  Keywords: reflection, pre-service English teacher, teacher education